2015
DOI: 10.1039/c4sc03748k
|View full text |Cite
|
Sign up to set email alerts
|

Emptying and filling a tunnel bronze

Abstract: We report the synthesis of a new tunnel-structured polymorph of V2O5 (ζ-V2O5) synthesized by topotactic ion extraction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 42 publications
(87 citation statements)
references
References 52 publications
(27 reference statements)
2
85
0
Order By: Relevance
“…It belongs to monoclinic space group C2/m with lattice constants of a = 10.07 Å, b = 3.60 Å, c = 15.2 Å, and β = 109.9° ( a = 11.7 Å, b = 3.62 Å, c = 8.84 Å, and β = 109.5°) . β′‐V 2 O 5 has been commonly labelled as ζ‐V 2 O 5 since the publication of a paper demonstrating its synthesis in a form of nanowires from β‐Ag 0.33 V 2 O 5 . Recent simulations predict the existence of two other phases: δ′‐V 2 O 5 (probably derived from δ‐K 0.5 V 2 O 5 or δ‐Sr 0.5 V 2 O 5 ) and ρ′‐V 2 O 5 .…”
Section: Vanadium Oxide Polymorphs: Structures and Raman Spectramentioning
confidence: 99%
“…It belongs to monoclinic space group C2/m with lattice constants of a = 10.07 Å, b = 3.60 Å, c = 15.2 Å, and β = 109.9° ( a = 11.7 Å, b = 3.62 Å, c = 8.84 Å, and β = 109.5°) . β′‐V 2 O 5 has been commonly labelled as ζ‐V 2 O 5 since the publication of a paper demonstrating its synthesis in a form of nanowires from β‐Ag 0.33 V 2 O 5 . Recent simulations predict the existence of two other phases: δ′‐V 2 O 5 (probably derived from δ‐K 0.5 V 2 O 5 or δ‐Sr 0.5 V 2 O 5 ) and ρ′‐V 2 O 5 .…”
Section: Vanadium Oxide Polymorphs: Structures and Raman Spectramentioning
confidence: 99%
“…Ternary vanadium oxide bronzes exhibit many unique structural and electronic properties . Their layered and tunnel structures facilitate the intercalation of a variety of cations, making them candidates for the next generation of Li‐ and multivalent‐ion battery cathodes . At the same time, this can lead to the creation of many unique V 2 O 5 bronzes (M x V 2 O 5 , M=Ca, Sr, K, Pb.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Their layered and tunnel structures facilitatet he intercalation of av ariety of cations, making them candidates for the next generation of Li-and multivalent-ion battery cathodes. [2,4,[5][6][7][8][9][10] At the same time, this can lead to the creation of many unique V 2 O 5 bronzes (M x V 2 O 5 , M = Ca, Sr,K ,P b. ), whiche xhibit multiple charge-ordered states, electronic correlation effects, and colossalm etal to insulator transitions.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the catalytic performance in the partial oxidation of H2S of metal-containing vanadium oxide bronzes strongly depends on the preparation procedure [12,13]. In the case of Na-promoted materials, it has been previously reported that mixtures of NaV6O15 and V2O5, containing 35 %, 66 % and 88 % of vanadium oxide bronze (determined by Rietveld from the XRD patterns) were achieved using Na/V ratios in the synthesis gel of 0.09, 0.17 and 0.33, respectively.…”
Section: General Remarksmentioning
confidence: 99%
“…Among them, Ag-containing vanadium oxide bronze has been extensively studied paying special attention their synthesis and characterization [13][14][15], but little is known about their catalytic properties [16,17]. In addition, the incorporation of divalent metals such as Ca or Cu could be of interest in order to modify physico-chemical properties of vanadium oxide bronzes.…”
Section: Introductionmentioning
confidence: 99%